DC and AC Performance of Graphite Films Supercapacitors Prepared by Contact Glow Discharge Electrolysis. Issue 12 (1st January 2017) - Allagui, Anis; Said, Zafar; Abdelkareem, Mohammad A.; Elwakil, Ahmed S.; Yang, Minghui; Alawadhi, Hussain
Abstract : In the present work, we fabricate and characterize carbon graphite films by high-voltage cathodic and anodic contact glow discharge electrolysis (CGDE) for supercapacitor applications. Transmission electron microscopy revealed that the carbon films obtained by anodic CGDE, in which a carbon graphite is used as the positive electrode, are in the form of two-dimensional, relatively large lateral size sheets without major fractures or structural distortions. Whereas with the cathodic configuration, tiny and elongated flakes of graphite attached to larger sheets are obtained. We observed negative Raman wavenumber shifts of the G peak and the appearance of the T peak at ca. 1100 cm − 1, which are attributed to thermal-induced strains and structural damages in the graphite crystal lattice, as well as to some C-C sp 3 bonds content. In addition to the aforementioned results and optical emission spectroscopy, it is proposed that both formation mechanisms by electrochemical exfoliation and material evaporation occur depending on the used polarization. All-solid-state symmetric supercapacitors using polyvinyl alcohol/H3 PO4 as gel electrolyte were fabricated and tested under dc and ac frequencies. We found two different behaviors: at dc and close-to-dc, the material prepared with cathodic CGDE showed close-to-ideal behavior with higher capacitance at different charging/discharging rates, which makes it more suitable for energy storage applications, whereas at higher frequencies ( ⩾ 100 Hz), the material prepared with anodic CGDE performed better for ac filtering applications that has been verified using an inverting integrator circuit.